2017
DOI: 10.1142/s0219025717500084
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Lévy differential operators and Yang–Mills equations

Abstract: Abstract:The relationship between the Yang-Mills equations and the stochastic analogue of Lévy differential operators is studied. The value of the stochastic Lévy Laplacian is found by means of Cèsaro averaging of directional derivatives on the stochastic parallel transport. It is shown that the Yang-Mills equations and the Lévy-Laplace equation for such Laplacian are not equivalent as in the deterministic case. An equation equivalent to the Yang-Mills equations is obtained. The equation contains the stochasti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…The last equality holds due to tr(P L (L W (t))Q S − (t)) = tr(P R (L W (t))Q S + (t)) = 0. Equality (32) implies the statement of the proposition.…”
Section: Definition 2 the Levy Trace Trmentioning
confidence: 70%
See 1 more Smart Citation
“…The last equality holds due to tr(P L (L W (t))Q S − (t)) = tr(P R (L W (t))Q S + (t)) = 0. Equality (32) implies the statement of the proposition.…”
Section: Definition 2 the Levy Trace Trmentioning
confidence: 70%
“…Another approach to the definition of the Levy Laplacian is to define it as the Cesaro mean of the second order directional derivatives along the vectors of some orthonormal basis (see [23,20]). This approach can be also useful in the connection with the Yang-Mills equations (see [28,30,32,35,36]) and instantons (see [29,34]). Different approaches to the Yang-Mills equations based on the parallel transport but not based on the Levy Laplacian were used in [17,15,13,14,8,9].…”
Section: Intoductionmentioning
confidence: 99%
“…With the help of such analogue it would be possible to develop the results of the paper Ref. [30], where the stochastic parallel transport was considered as a general chiral field. Also it would be interesting to investigate the connection between the stochastic Lévy Laplacians introduced in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…In Refs. [30,31] the Levy Laplacian defined as the Chesaro mean of the directional derivatives in the stochastic case was studied. 2 It was shown that, unlike the deterministic case, the equivalence of the Yang-Mills equations and the Levy-Laplace equation is not valid for such Laplacian.…”
Section: Introductionmentioning
confidence: 99%
“…In the deterministic planar case, it has been shown in work [29] that this is indeed the case (see also [7]). In the author's work [31], using the Malliavin calculus, the Lévy Laplacian, defined as the Cesàro mean of second partial derivatives, has been introduced on the Sobolev space over the Wiener measure and its relation to gauge fields has been studied. It should be noted that, unlike the deterministic case, the Lévy Laplacians on the Sobolev spaces over the Wiener measure, introduced in the works [22] and [31], operate in different ways.…”
Section: Introductionmentioning
confidence: 99%